Code-Switching and Code-Mixing in Buying and Selling Activities at The Sapeken Traditional Market Sumenep – Madura Regency (A Sociolinguistic Study) - Suka, Eva; Budasi, I Gede; Adnyani, Ni Luh Putu Sri (Journal of Educational Study, 2024)
This research aims to know the language forms about code switching and code mixing that happened between sellers and buyers in the Sapeken traditional market. This research discusses about the language form of code switching and code mixing, and the types of code switching and code mixing, and the factors which influence the use of code switching and code mixing in buying and selling activities at the market. It applied a descriptive qualitative research. The subjects of the research are sellers and buyers. The object of the research is code switching and code mixing the use in their interaction. The types of data in the study were use qualitative data and primary the source of the data. The obtained data of the study were collected though recording and note-taking technique. This studied concluded that the speech community in the market were found using five different languages: Bajau, Mandar, Madurese, Javanese, and Indonesian, however when the do code switching and code mixing, they used language other than Indonesian. Their forms of code switching varied from Indonesian with Bajau languages, Bajau with Madurese languages, Bajau with Mandar languages, and Bajau with Javanese languages. Futhermore, the forms of code mixing varied from Indonesian with Bajau languages, Bajau with Javanese languages, Madurese with Bajau languages, and Bajau with Mandar languages. Before that, the types of the code switching used by the speech community of the traditional market are in the category of Intra-sentential, Inter-sentential, and Tag-switching. While, the types of code mixing, their use Insertion, Alteration, and Congruent Lexicalization. The last one, the factors which influence the use of the code switching were the Speakers, Interlocutor, and the Third-person Attendance. Whereas, the factors which influence the use of code mixing were the Social, Cultural, and Individual factors.